Analisis Kualitas Modul UNAI Terhadap Kepuasan Pengguna Dengan WebQual 4.0 dan Importance Performance Analysis (IPA) - Gabriel Putra Advent Yakop Sihombing; Jay Idoan Sihotang (J-ICON : Jurnal Komputer dan Informatika, 2022)
In the current digital era, technology is developing very rapidly where the role of internet technology is increasingly influential because all activities can be carried out on the internet. Many universities use the website as an information medium to provide the information needed for students in their academic needs. The purpose of this study was to measure the level of quality of the academic information system at the Adventist University of Indonesia (UNAI) at the level of quality of use using the WebQual 4.0 approach. WebQual is a framework with techniques for measuring website quality by compiling user perceptions based on four existing dimensions, namely usability, information quality, services interaction quality and overall impression. The population in this study were students at UNAI who used the unai module. Samples were taken as many as 94 respondents. This research was conducted using a WebQual 4.0 dimension approach by distributing to respondents based on four WebQual 4.0 dimensions and conducting an analysis with importance performance analysis (IPA) with the aim of getting the level of user satisfaction then the results of the analysis of the academic information system at UNAI are still not suitable for user satisfaction where there are 4 items in the A quadrant, namely items U5, IntQ19, Int21, and OI22. Suggestions that can be given to website owners are to be able to add chat forum features, chat boxes and live chat.